Beyond national literatures: Empire and Amitav Ghosh - Maxey, Ruth (Cambridge University Press, 2016)
Scholarship on the writer Amitav Ghosh has addressed issues of nationalism, postcolonial identity, ecocriticism, testimony, subalternity, and historiography. But the idea of Ghosh as an Asian American author with a particular relationship to the United States and its national mythologies, has barely been considered. In this essay, I explore this neglected aspect of Ghosh’s œuvre by looking at the idea of America in his writing and by situating his work within what I term "the Bengali American grain". Reading his work alongside that of other Bengali American writers and arguing that it is more ambitious thematically and more anti-imperialistic, I probe Ghosh’s problematic relationship with the United States, asking how his hemispheric writing continues to extend and even alter the terrain often associated with Asian American literature.